Biserica de lemn „Sfinții Arhangheli Mihail și Gavriil” din Drăghia - Cotețiu, Marin (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
In this paper I present a part of the research I carried out for the elaboration of the restoration project of the mural painting and of the iconostasis of the wooden church from Drăghia village, Maramureş county. I start by presenting some data about the history of the church, then I describe the architecture of the church, the mural painting and the iconostasis. The description of the church painting contains information about the iconography, the artistic technique and the state of preservation of the painting. The text is accompanied by photos.